Gender perspective on entrepreneurial intentions and innovation cognitive style: cross-country study - Mirjana Pejic-Bach; Peter Sasvari; Marjana Merkac Skok; Rajeev Dwivedi; Lee Wai Yee; Vanja Šimicevic; Karmen Abramovic (Knowledge and Business Challenge of Globalisation in 2012: 4th International Scientific Conference, 2012)
A number of researchers indicate that although environmental and personal characteristics are important for developing entrepreneurial intentions, a better understanding would be gained if innovative cognitive style, as a moderating factor, would be introduced. According to theory, individuals with high innovative cognitive ability could also have higher entrepreneurial inentions. Persons that are more innovative, could have higher selfconfidence in starting a business, especially if they are not satisfied with their current jobs, or expect that they will not be satisfied as employees in organizations. In addition, in a number of studies it has been found that there are unresolved issues regarding gender and entrepreneurial intensions and gender and innovative cognitive style. Therefore, the goal of our paper is to explore gender perspective on entrepreneurial intentions and innovative cognitive style on the sample of students from Croatia, Slovenia, India, Hungary and Hong Kong. Logistic regression revealed that entrepreneurial intentions are determined by country of origin, gender, attitudes toward entrepreneurship (personal attraction, social norms, and perceived self-efficacy), and innovative cognitive style (willingness to try, being opinion leader and solving ambiguities and problems).
Keywords: M15; M13; 330; gender; innovation; cross-country; intentions; entrepreneurship